Household and Individual Economic Responses to Different Health Shocks: The Role of Medical Innovations - Volha Lazuka (Institute of Labor Economics (IZA), 2023)
This study provides new evidence regarding the extent to which medical care mitigates the economic consequences of various health shocks for the individual and a wider family. To obtain causal effects, I focus on the role of medical scientific discoveries and leverage the longitudinal dimension of unique administrative data for Sweden. The results indicate that medical innovations strongly mitigate the negative economic consequences of a health shock for the individual and create spillovers to relatives. Such mitigating effects are highly heterogeneous across diagnoses that cause health shocks. These results suggest that medical innovations substantially reduce the burden of welfare costs yet produce income inequalities.
Keywords: I14; I18; J22; J24; J38; O31; 330; medical innovation; health shock; family disposable income; income inequality; difference-in-differences-in-differences approach; machine learning